An Empirical Analysis of the Relationship among Corporate Social Responsibility, Innovation, and Corporate Performance in Developing Countries - SUN, DI (2020)
This paper mainly studies the relationship among corporate social responsibility, innovation, and corporate performance in developing countries. Data from 150 companies in 12 developing countries from 2014 to 2019 were collected from Datastream, Bloomberg, and the World Bank website. Excel and STATA were used to process the obtained panel data. Then the fixed effect model and random effect model were used to carry out regression analysis on 15 models proposed according to the hypotheses. The results show that for developing countries: (1) there is no significant relationship between corporate social responsibility and innovation. This conclusion is different from the conclusions put forward by most previous studies and may be related to the corporate social responsibility measurement methods and sample selection. (2) Corporate social responsibility has a positive impact on corporate performance. This paper subdivides corporate social responsibility into three categories, among which the positive relationship between environmental social responsibility and governance social responsibility is the most significant. It shows that stakeholders are concerned about environmental issues and governance issues, which directly affect their decisions. (3) Innovation and corporate performance have positive impacts on each other. Enterprise innovation could bring the improvement of corporate performance, and good corporate performance will also promote innovation, forming a virtuous circle. (4) Innovation has a positive moderating effect on the relationship between corporate social responsibility and corporate performance. When the direction of innovation is consistent with corporate social responsibility, the positive role of corporate social responsibility in promoting corporate performance could be enhanced. Keywords: Corporate social responsibility; innovation; corporate performance